A transzeurópai hálózatok hatása a területi fejlődésre - Erdősi, Ferenc (Tér és Társadalom, 1998)
The article aims at addressing the issue of the Transeuropean Network (TEN) and Paneuropean Network (PEN) and their impact on regional economic development in Europe. The chief goal of this study is to highlight the fact that these developments, in reality, are not in tandem with those affects which are „offícially" planned by policy-makers. Perhaps, the most significant problem with TEN and PEN is the fact that a complex plan, including the most important principles of spatial development, for developing European transport networks has not been produced yet. The lack of this plan cannot be substituted by the existing documents which outline 7 development principles for TEN and the 10 complex transport corridors and 4 high-priority transport areas for PEN. The other great challenge is how to handle those regional inequalities between regions which are close to the transeuropean corridors and those located further from them, which come to life after the transeuropean networks are in place. There seems to be a danger that national and European regional policies cannot resolve but can only alleviate these inequalities.